1988
DOI: 10.1111/j.1471-0528.1988.tb06501.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal fetal heart rate variation in relation to the respiratory and metabolic status of the compromised human fetus

Abstract: Summary. Three groups of women were delivered by caesarean section before labour: for an abnormal fetal heart rate (FHR) trace (21 cases, group 1), or for maternal deterioration in severe pre‐eclampsia without gross fetal heart rate abnormalities (20 cases, group 2), or to avoid mechanical difficulties in labour at term (30 cases, group 3). The mean gestational ages of the first two groups were 32 weeks with a high proportion of infants small‐for‐gestational‐age. In group 1, FHR variation (mean range of pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(62 citation statements)
references
References 44 publications
4
55
1
2
Order By: Relevance
“…The computer analysis of the FHR tracing, developed by Dawes et al [1,2], is one of the prevailing quantification methods. It has been validated by comparing computer FHR analysis results with fetal blood gases obtained via funipuncture or cord blood at cesarean birth before labor [3,4]. However, it is not thoroughly elucidated from a physiological point of view what attributes to the FHR variations.…”
Section: Introductionmentioning
confidence: 99%
“…The computer analysis of the FHR tracing, developed by Dawes et al [1,2], is one of the prevailing quantification methods. It has been validated by comparing computer FHR analysis results with fetal blood gases obtained via funipuncture or cord blood at cesarean birth before labor [3,4]. However, it is not thoroughly elucidated from a physiological point of view what attributes to the FHR variations.…”
Section: Introductionmentioning
confidence: 99%
“…They found minor degrees of respiratory acidemia and concluded that abnormal CTG traces may be associated with hypoxia, but were unrelated to asphyxia. 13 We compared two groups of patients based on CTG and found no significant difference between the fetal-distress and normal groups in terms of umbilical cord blood gas findings and Apgar scores. The most important limitation of our study was the small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the positive and negative predictive values were 81% and 89%, respectively, for decelerations and 88% and 76%, respectively for variability loss. 13 Smith et al (14) analyzed the umbilical cord arterial blood gas in 21 patients undergoing a cesarean section because of abnormal CTG. They found minor degrees of respiratory acidemia and concluded that abnormal CTG traces may be associated with hypoxia, but were unrelated to asphyxia.…”
Section: Discussionmentioning
confidence: 99%
“…Other findings seen with IUGR compared with normally developed fetuses include an elevated fetal heart rate (FHR) and lower short/long term variability. [11][12][13][14][15][16][17][18] Although central nervous system maturation is delayed, centrally regulated responses to hypoxia remain preserved. 17 With fetal hypoxemia, there will be a decrease in overall fetal activity, a progressive loss of individual biophysical profile components, and often a gradual decline in amniotic fluid volume.…”
Section: Behavioral Responsesmentioning
confidence: 99%